No. 6. Volume 9 - Asano, Atsuko, 1954- (Kodansha Comics, 2014)
With Rat critically injured protecting him, Shion finally returns to No. 6. But what he finds there is not the tranquil utopia he left behind, but a city in the grip of panic and chaos. As the 'holy city' collapses in on itself, Shion and Rat put the future of humanity-- and their future together-- on the line in the shocking final volume!"--P. [4] of cover.